Pb-Zn-Ag DEPOSITS AT TANJUNG BALIT, LIMAPULUH KOTA REGENCY, WEST SUMATERA - Z.Abidin, Hamdan (Jurnal Geologi dan Sumberdaya Mineral, 2008)
A Pb-Zn-Ag deposit located at Tanjung Balit, Limapuluh Kota Regency, West Sumatra, is hosted within the meta sedimentary rocks of the Tapanuli Group. The lithology consists of interbedded shale, meta sandstone, slate and phyllite (Kuantan Formation). The deposit is in the form of veins, veinlets and disseminated. The thickness of veins ranges from few centimeters up to 5 meters.  In places, some ore bodies are conformable with the host rocks. The main ores are lead, sphalerite, chalcopyrite, pyrite and silver with minor marcasite, magnetite, chalcosite and gold. Hydrothermal mineral assemblages consist of silica, illite, monmorillonite, pyrophyllite, muscovite, siderite, diaspore, dickite, magnesite, chlorite, carbonate, rhodochrosite, analcime, alunite, smectite, ankerite, calcite, dolomite, sericite and zeolite. Fluid inclusion measurements of secondary inclusions within quartz veins indicate that the homogenization temperature (Th) ranges from 185 - 350ºC. The presence of alunite, higher content of base metals as well as higher temperature range of the secondary fluids suggests that the deposit may characterize a high suphidation epithermal type. Keywords : Tanjung Balit, Tapanuli Group, fluid inclusion,  high sulphidation epithermal